Assessing Internal and External Determinants of Bank Profitability: A Study on Indonesian Regional Development Banks - Hapsari, Pascalista Dwi; Ramadhanti, Fina Setya; Ristianawati, Yuyun; Prasetyanto, Wahyu Eko; Jumadi, Muhamad (Global Health Science Group, 2024)
This study explores what drives profitability in Indonesia’s Regional Development Banks (RDBs), focusing on both internal and external factors. Using financial data from 10 Islamic commercial banks over the 2014–2019 period, the research applies multiple linear regression to assess how capital adequacy, liquidity risk, and financing risk—alongside GDP and inflation—affect bank performance. The results show that strong capital adequacy supports higher profitability, while liquidity and financing risks can significantly reduce it. Notably, financing risk also acts as a bridge between internal factors and profitability outcomes. On the macroeconomic side, GDP growth tends to boost profitability, whereas rising inflation has a negative impact. These findings highlight the importance of solid internal risk management and a stable economic environment. For bank leaders, maintaining sufficient capital and minimizing financial risks is essential. For policymakers, supporting economic growth and keeping inflation under control can directly influence the health of the banking sector